1988
DOI: 10.1002/hep.1840080410
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro transmission of duck hepatitis B virus to primary duck hepatocyte cultures

Abstract: An attempt was made to infect primary duck hepatocyte cultures with duck hepatitis B virus in vitro in order to clarify the biology of hepatitis B virus. Livers of ducklings, 0 to 17 days posthatch, without viremia were digested ex situ by perfusion of collagenase solution through the portal or hepatic vein. Homogeneous hepatocyte suspensions were seeded into plastic dishes in L-15 medium containing 10(-8) M insulin, 2 X 10(-8) M glucagon and 10(-8) M dexamethasone and were subsequently inoculated with suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…showed that while virus DNA became identifiable at the end of a 24-h incubation with virus, cccDNA was first detected at day 1 or 2 p.i. This delayed appearance of cccDNA in WCM-260 hepatocytes is consistent with the previous observations on WHV and duck HBV virus (DHBV) replication in primary woodchuck or duck hepatocytes (1,3,31,40,41). It was postulated that this postponement in cccDNA formation could be a consequence of various intracellular processes, which may include inefficiencies in virus genome uncoating and/or nucleocapsid translocation to the nucleus, a requirement for accumulation of the virus products controlling cccDNA assembly, or be due to an intrinsic inefficiency of the cell cultures employed (1,9,31).…”
Section: Discussionsupporting
confidence: 92%
“…showed that while virus DNA became identifiable at the end of a 24-h incubation with virus, cccDNA was first detected at day 1 or 2 p.i. This delayed appearance of cccDNA in WCM-260 hepatocytes is consistent with the previous observations on WHV and duck HBV virus (DHBV) replication in primary woodchuck or duck hepatocytes (1,3,31,40,41). It was postulated that this postponement in cccDNA formation could be a consequence of various intracellular processes, which may include inefficiencies in virus genome uncoating and/or nucleocapsid translocation to the nucleus, a requirement for accumulation of the virus products controlling cccDNA assembly, or be due to an intrinsic inefficiency of the cell cultures employed (1,9,31).…”
Section: Discussionsupporting
confidence: 92%
“…DHBV-positive PDHs were obtained by infecting day-old Pekin-Aylesbury ducklings with DHBV (strain D16). Seven days later, duckling livers were collagenase perfused as previously described (31). PDHs were maintained in Williams E medium with 10 mM Tris, pH 7.6, 6 mM HEPES, 0.02% sodium bicarbonate, 1% penicillin, 1% streptomycin, 1% glutamine, 0.02% glucose, 10 M hydrocortisone 21-hemisuccinate, 0.01% insulin, and 1.5% dimethyl sulfoxide.…”
Section: Methodsmentioning
confidence: 99%
“…Primary duck hepatocytes (PDH) were used to quantify the infectious virus titer according to a modification of a previously described method (1). PDH were prepared by collagenase perfusion of 7-day-old PekinAylesbury ducklings, as described previously (52). DHBV-negative PDH were grown on glass coverslips for 48 h. Apical and basolateral supernatants from BeWo transcytosis experiments were clarified by centrifugation.…”
Section: Methodsmentioning
confidence: 99%